Pengaruh Latihan Skipping Terhadap Hasil Shooting Permainan Sepak Bola di MTs Pui Kasturi - Reza Moh Zaen (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to determine the effect of skipping practice on shooting results in football games at MTs Pui Kasturi. The research method used is an experiment with a quantitative approach. The subject of the study was students who were members of the school football team. Skipping exercises were given as an intervention over a period of time, and the shooting results were measured before and after the intervention. The results showed that there was a significant increase in shooting results after being given skipping exercises. This shows that skipping practice can be one of the effective methods to improve shooting skills in football.